The Acceptance Study of e-commerce Customers Based on TAM - Rainaldo Diogenes Susilo; Benny Daniawan; Andri Wijaya; Suwitno Suwitno (bit-Tech, 2021)
The improvement of information technology and science has grown rapidly. CV. Sukses Mandiri Jaya, which is engaged in the sale of spare parts for motorcycle, does not have a computerize system, making it difficult for buyers to see the products and to make transactions. The work aim to create a web based system with the Technology Acceptance Model (TAM) to measure the usability level of the system. TAM is used to achieve a certain goal by identifying some of the basic variables and by measuring factors that affect system acceptance. TAM positions two beliefs, that are Perceived Usefulness and Perceived Ease of Use as major factors in system acceptance behavior. It was found that the proposed system accepted by customers, which was measured by a questionnaire involving 57 respondents. The results show that Perceived Usefulness and Perceived Ease of Use simultaneously and partially have positive and significant influence on the Behavior Intention. This also shows that result of the relative contribution of perceived usefulness (X1) is 36.75% and the perceived ease of use (X2) is 63.25%. The effective contribution of Perceived Usefulness is 29.44% and the Perceived Ease of Use is 50.66% for Behavior Intention, which means that the effect of Perceived Ease of Use is more dominant than the Perceived Usefulness